Caracterização morfológica das anfisbenas sul-americanas de cabeça levemente comprimida e não quilhada (Amphisbaenia: Amphisbaenidae) com a descrição de uma nova espécie - OLIVEIRA, Elaine Cristina da Silva (Universidade Federal do Oeste do Pará, 2021)
Amphisbaenia is a monophyletic member of the Amphisbaenidae, represented word-wide by 197 valid species, of which 73 occur in Brazil. Overall, Brazilian Amphisbaenid diversity involved three genera in this family: Mesobaena (1 sp.), Leposternon (9 spp.) and Amphisbaena (63 spp.). The latter genus is the most morphologically diverse. Amphisbaena includes species with rounded heads, slightly compressed, unkeeled, broad, strongly keratinized, and slightly flattened. There are currently 14 Amphisbaena species with slightly compressed, unkeeled heads, of which 12 occur in Brazil, one in Bolivia and one in Puerto Rico. This study was carried out in order to update data on the external morphology and geographic distribution of the South American species with this characteristic, and to describe a new taxon with a slightly compressed and unkeeled head for the Brazilian Amazon. Twenty two meristic data and 49 morphometric variables from 157 specimens of this species group were analyzed, including seven holotypes. To test which meristic and morphometric characters distinguished best between the species, and to test between-population variation with species a Discriminant Analysis of Principal Components - DAPC - was developed. Differences in main coordinate values per individual between species were tested using a combination of Analysis of Variance (ANOVA) and Tukey tests. A total of 637 specimens from thirteen species of Amphisbaena with lightly compressed and unkeeled heads (except A. xera) were sampled from the principle Brazilian collections. Of this, 67.6% (n = 431 specimens) belong ed to three species: Amphisbaena brasiliana (n = 194); A. roberti (n = 127) and A. saxosa (n = 110). Additional information in geographical distribution was gained for: A. borelli, A. brasiliana, A. cuiabana, A. roberti and A. steindachneri. Analyzes indicated that the species studied are morphologically distinct for meristic and morphometric characters and should all be treated as valid taxa. Amphisbaena roberti and A. steindachneri had intraspecific variation. Within the analyzed sample of Amphisbaena brasiliana sufficient meristic and morphological variation was found for a new taxon. Amphisbaena sp. nov. to be described. It is characterized by having four precloacals pores arranged in sequence,247–252 dorsal half-annuli; 27 caudal annuli; autotomy site present on the 7th or 8th caudal annuli; three supralabials; postmalar row absent; and, occipital absent.